A Survey on the Presence of Calcifying Nanoparticles in Renal Stones, Gallbladder Stones and Atherosclerosis Plaque - A Izadi; E Moslemi (Journal of Kerman University of Medical Sciences, 2014)
Background & Aims: Calcifying nanoparticles are different forms of calcium and phosphate in sediments. Recent evidence suggests that calcifying nanoparticles (CNPs) are probably selfreplicating. Several diseases are linked to nano-bacteria including kidney stones, gallbladder stone, cardiovascular plaques, oral–dental plaque, many cancers, and autoimmune diseases. The aim of this study was to assess the presence of nano-bacteria in kidney stones, gallbladder stones, and atherosclerosis plaques and compare them with each other in terms of structural form. Methods: In this study, 18 samples of kidney stones, 15 gallbladder stones, and 11 samples of atherosclerosis plaque, taken by surgeons during surgery, were collected. After isolation of nanobacteria (NB) from the sample and confirmation by scanning electron microscope (SEM), some of the samples were cultured in a solution of Dulbecco's Modified Eagle Medium (DMEM) containing fetal bovine serum (FBS) 10% and glutamate at 37 °C with 5% CO2 and 95% air for 8 weeks. Deoxyribonucleic acid (DNA) extraction protocol was performed in all samples. After that, they were analyzed by polymerase chain reaction (PCR) techniques. Results: 17 cases out of 18 kidney stone samples were culture positive. Moreover, 14 cases out of 15 gallbladder stone samples and all 11 samples of atherosclerosis plaque were culture positive. Growth and the presence of CNPs were confirmed in all cases by SEM. PCR testing was performed for all samples; however, no DNA samples were detected with the primers used. Conclusion: According to the results, the presence of calcifying nanoparticles using culture methods, and observation using scanning electron microscope were confirmed. However, the existence of nucleic acid has not been confirmed in this study. Thus, more research using PCR must be performed to prove their existence. Therefore, we can say that one of the important factors in the development of kidney stones, gallbladder stones, and atherosclerosis plaques is the presence of microorganisms.